Participative Leadership in Indonesian Education: A Systematic Literature Review - Retno Rahayuningsih; Ary Iswanto Wibowo; Sayyid Khairunas (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to systematically review the implementation of participatory leadership in Indonesia's educational context, across schools and higher education institutions, using a Systematic Literature Review (SLR) guided by the PRISMA framework. This research collected and analyzed studies from Google Scholar, Scopus, and Web of Science. Of the 780 articles screened, 15 were selected for final analysis. The results reveal that participatory leadership positively influences teacher and lecturer performance, enhances organizational commitment, and fosters innovation. For instance, participatory leadership and teacher motivation accounted for 86% of the improvement in school quality. Several models were identified, including collective, consensus-based, and democratic models, often overlapping with adaptive leadership. Despite its benefits, challenges such as limited leadership capacity and inconsistent implementation persist. This study contributes theoretically by expanding knowledge of educational leadership models and, practically, by offering evidence-based recommendations for academic leaders and policymakers. The findings provide a basis for creating more inclusive and collaborative environments to improve student learning outcomes and institutional performance.